Die Chemie des Tetracyanäthylens - R. Winkler (CHIMIA)
The most convenient method for the preparation of tetracyanoethylene is to react dibromomalonitrile with copper powder in boiling benzene solution. The high melting tetracyanoethylene is a mild oxidizing agent and its double bond is highly electron deficient. Thus it acts as an electron acceptor, reacting with systems containing an excess of π-electrons, such as aromatic hydrocarbons, to form coloured charge transfer complexes. With 1,3-dienes, ketones with α-hydrogen atoms and reducing agents, it gives rise to addition products. With nucleophilic reagents such as alcohols, bases, aromatic hydrocarbons and heterocyclics rich in electrons, it undergoes substitution reactions, whereby one or two nitrile groups may be substituted. Subsequent reactions starting from these different products lead to new heterocyclic systems, strong acids, dyes, luminescent compounds and polymers for different technical applications.